Is harmonisation of VAT rates still necessary in the European Union? (Economic and Political Thought, 2018)
For more than 20 years, a principle of taxation of goods and services inthe state of destination has been in force in the European Union – VAT islevied according to the rate applied in the state of the purchaser of goods.The principle was introduced due to, inter alia, the differences in the VATrates in individual Member States, and was planned to operate temporarily,especially until the VAT rates harmonisation process is completed. Theintended “definitive” VAT regime was based on the principle of taxation inthe Member State of origin, i.e. at the rate applicable in the country of thesupplier. The recently published Commission Communication announcedseveral actions towards the change in the rules on taxation of the cross--border transactions so that the suppliers could levy VAT on the purchaserssimilarly as it happens in case of domestic transactions, i.e. in accordancewith the rates applicable in the state of destination of goods. The Articleaims to present the general conclusions on the results of the research intothe need to harmonize the rates, particularly in the light of the latest plansof the Commission.
Keywords: VAT, VAT rates, VAT harmonisation, cross-border transactions